URGENSI PERLINDUNGAN PENGETAHUAN TRADISIONAL SECARA SUI GENERIS DALAM REZIM HAK KEKAYAAN INTELEKTUAL INDOENSIA - Wicaksono, Galih Wahyu (JURNAL DARMA AGUNG, 2022)
Indonesia has inherited by lot of biodiversity, it cannot be separated from the Cultural Expressionsand Traditional Knowledge possessed by the local communities. The existence of this giving createsthe potential that generate economic profits as well as the potential for the emergence of biopiracyand misappropriation activities carried out by the other parties. This research aims to analyze andunderstand the concept of traditional knowledge and the urgency of establishing sui generis lawsrelated to the protection of traditional knowledge. The method of this research uses normativejuridical methods. The researc h results concluded that traditional knowledge has an open natureis generally aimed at human itarian activities, and is not far from spiritual or religious. Eventhough there is a law related to Intellectual Property Rights that protects traditional knowledge,it has not been effective in protecting the rights of traditional knowledge owners. Due to this, it isnecessary to establish a sui generis law related to the protection of traditional knowledge to providejustice and protection from biopiracy and misappropriation activities.